Exploring the efficacy of crab shell-based biochar for adsorptive uptake of Bromocresol purple dye in a textile wastewater: kinetics and mechanistic studies - Ndive, Julius N.; Onukwuli, Okechukwu D.; Obiora-okafo, Ifeoma A.; Nnabuife, Somtochukwu Godfrey; Kuang, Boyu (Avanti Publishers, 2025)
High-quality adsorbent derived from Crab Shell Activated Biochar (Fe₂O₃@BC) was effectively synthesised from discarded crab shells (CS) for the adsorptive elimination of Bromocresol purple colour (BCP) from textile wastewater. The structure of crab shell biochar (CSB) and crab shell activated biochar (CSAB) was looked at using SEM, and the light properties of the samples made from CSAB were checked with FTIR. The characterisation results suggested that the extracted chitin exhibited substantial properties necessary for surface phenomenon-driven matrices. This study looked at how well crab shell activated biochar and crab shell biochar can remove Bromocresol Purple (BCP) dye from water, finding that CSAB works better than CSB. The adsorption tests were conducted at varying pH levels, varied adsorbent doses, temperatures, and contact durations in batch trials. The kinetic analysis demonstrates that the removal efficiency was optimal according to the pseudo-second. The Weber–Morris intraparticle-diffusion analysis identified three operative adsorption sites. This low-cost crabshell-activated biochar, characterised by its advanced pore structure, distinctive surface properties, and superior adsorption capabilities, has the potential to function as an effective adsorbent for dye removal in textile effluent.
Keywords: 4105 Pollution and Contamination; 40 Engineering; 41 Environmental Sciences; 4004 Chemical Engineering; 4011 Environmental Engineering